SAYED HAIDER RAZA -A CELEBRATION OF NATURE - Thakur, Meenakshi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Art is basic human activity rooted in his nature and history of all civilizations. From time to time many philosophers have tried to define art, but their definitions are varied as life and nature themselves are. Art can teach research much about a culture. It illustrates a people’s views about beauty, morality, religion, and many other topics. The emphasis of this research is on the contribution of PAGs most influential artist S.H Raza, in the development of contemporary Indian art. His paintings are extremely attractive and full of colour which represents the celebration of nature through rich and vibrant color which represents the continuous experimentation of an innovative and imaginative personality, who is not satiated with his past Laurels alone and is continuously experimenting with new forms, makes them highly appealing, attractive, and timeless and source of inspiration for art faculties and art Connoisseurs.